Students’ Perception as Teacher Candidate in Applying Learning Process with Research Based and Character Based - Chalimah Chalimah (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
Teacher candidates have essential role to assist in developing learning process and in achieving character building since they play role as teacher candidate and also as students. The research gap is to find out the students’ perception as teacher candidate about learning process with research based as well as character building achievement based on their real experience. The research instrument is open questionnaire which is shared through WhatsApp. The finding shows that 80% of teacher candidates supports learning process with research based, 10% of teacher candidates less supports learning process with research based, and 10% teacher candidates rejects learning process with research based. The students as teacher candidates as much as 70% describes that the character education has been well achieved and 30% of them states that the character education has not been achieved.